Tribunal do júri: Constituição do ethos e orientação argumentativa - PINTO, Walber Neto Lopes (2023)
The Jury Court is an institute that judges crimes of intentional nature against life, where the defense will be used as a methodology to promote the equality and honesty of the jury. The speech welcomed in the rite of the Jury Court, adopts argumentative strategies that collaborate for the construction of the ethos, which can be projected in the auditorium according to the speech, persuasion and conduction of the speaker, in order to elaborate the profile with the interlocutors and auditorium. The problem was: What are the argumentative strategies in the speech adopted in the Jury Court that allow deliberating on criminal issues? The objective was to analyze the argumentative strategies in the legal discourse, in order to unveil the images constructed by the participants of the trial in the Jury Court. The methodology was based on a bibliographical review, followed by the analysis of the corpus of a session of judgment of crimes against life in the city of Bacabal - MA, with analysis of the speech of the participants of the judicial rite, in order to evaluate the construction of the profile of the defendant and the speakers, which allows to gain the adhesion and credit of the jury. The procedures and strategies employed allowed the elaboration of the ethos of the judgment that incited the audience's empathy and acceptance of the theses presented to the specific case. It was concluded that the Jury Court and the defense facilitate the process of gaining respect and enforcement of the defendant's rights through legal instruments and a speech, with a theoretical conception of rhetoric, argumentation, ethos and the Sciences of Law.